Peptide receptor radionuclide therapy in the management of neuroendocrine tumors (Neoplasms)*: Fundamentals and salient clinical practice points for medical oncologists - Sandip Basu; Rahul Parghane; Rohit Ranade; Pradeep Thapa; Anant Ramaswamy; Vikas Ostwal; Bhawna Sirohi; Dipanjan Panda; Shailesh V Shrikhande (Indian Journal of Medical and Paediatric Oncology)
This editorial commentary is an expert summary of “Peptide Receptor Radionuclide Therapy (PRRT),” encompassing the essential fundamentals and salient clinical practice points, deliberated and designed in a point-wise manner with theme-based subheadings. Emphasis has been laid on the topics of practical relevance to the referring oncologists with relevant finer points where necessary. A part of the presented overview has been generated from the authors' own practical experience of more than 3500 successful therapies delivered over the last 9 years at a large tertiary care PRRT setting by the joint efforts of Radiation Medicine Centre (RMC), Bhabha Atomic Research Centre (BARC), and Gastrointestinal services of Tata Memorial Hospital (TMH) at the TMH-RMC premises. While the technical indigenization is beyond the scope of this treatise, we must mention here that India had been one of the frontrunners in this treatment modality, and the PRRT services in this country were developed purely as an indigenous effort right from the production of the radionuclide (177-Lutetium) at the reactor and radiolabeling and production of the radiopharmaceutical (177Lu-DOTATATE) by the radiopharmaceutical scientists at the BARC and RMC; such an endeavor allowed this very specialized therapy to be delivered at a very affordable cost in our setting which could be viewed as a major societal contribution of the atomic energy research in this country.